Subject trend analysis of theses submitted to the U.P. Institute of Library and Information Science, 1981-2000 - Gapas, Amor C. (2005)
This study was conducted to find out the current trend in library science research submitted to the U.P. Institute of Library and Information Science in terms of topics chosen for study. The study covered a total of 378 theses, both of undergraduates and graduate students, from 1981 to 2000. The researcher employed simple statistics and tabulation in the presentation and analysis of data.